2022
DOI: 10.3390/toxins14090635
|View full text |Cite
|
Sign up to set email alerts
|

A Uremic Pig Model for Peritoneal Dialysis

Abstract: With increasing interest in home dialysis, there is a need for a translational uremic large animal model to evaluate technical innovations in peritoneal dialysis (PD). To this end, we developed a porcine model with kidney failure. Stable chronic kidney injury was induced by bilateral subtotal renal artery embolization. Before applying PD, temporary aggravation of uremia was induced by administration of gentamicin (10 mg/kg i.v. twice daily for 7 days), to obtain uremic solute levels within the range of those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Importantly, this approach preserves the retroperitoneal anatomic planes and vasculature, facilitating straightforward exposure of the iliac vasculature for anastomosis of the SNMHD or other implantable, blood-based renal replacement technologies. Compared to the approaches described by de Vries [22] and Misra [24], our approach offers at least two distinct advantages. First, both groups reported fatal or euthanasia-requiring complications associated with their single-stage embolization procedures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, this approach preserves the retroperitoneal anatomic planes and vasculature, facilitating straightforward exposure of the iliac vasculature for anastomosis of the SNMHD or other implantable, blood-based renal replacement technologies. Compared to the approaches described by de Vries [22] and Misra [24], our approach offers at least two distinct advantages. First, both groups reported fatal or euthanasia-requiring complications associated with their single-stage embolization procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Misra and colleagues found that single-stage bilateral endovascular nephrectomy can produce mobility-limiting pain and an overwhelming inflammatory response that is life-threatening for the animal [ 24 ]. Recently, a similar endovascular nephrectomy protocol has been used to induce uremia in swine for the study of novel peritoneal dialysis therapies [ 22 ]. The same group has also developed an acute-on-chronic goat model of kidney injury using a combination of endovascular nephrectomy and gentamicin-induced kidney injury with animals surviving for 10 months; a procedure which may be advantageous for studying chronic dialysis therapies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations